(untitled) (Stavební obzor - Civil Engineering Journal, 2015)
It is well know that freeze-thaw cycles play the most significant role in the durability evolution in concrete structures, freeze-thaw cycles have been accounted as one of the major factors on the damage and demolition of concrete. Microscopic parameters have been used for describing the characterizations of damage in concrete under freeze-thaw actions by researchers. However, their models could not provide specific damage factors or parameters. In this paper, a new damage model and equation based on variations of pore structure in concrete is established. This new pore damage model is used for analysing freeze-thaw damage of concrete and validated by experiments. The results show that the measurement of pore structure becomes larger, the diameters of most probably pore structure, critical pore structure, and the variations of porosity increase with the process of freeze-thaw cycles. The pore damage factor or parameter is suitable for describing the mechanism of freeze-thaw damage. Furthermore, the damage results calculated by this new freeze-thaw damage equation, based on variations of pore structure in concrete gives an excellent correlation with experimental results. This pore damage equation was proved to be effective for evaluating the degradation of concrete which is subjected to freezing and thawing cycles in low or sub-zero regions.